Efficacy and safety of metformin for melasma treatment: a systematic review and meta-analysis - Mongkhon, Pajaree; Ruengorn, Chidchanok; Awiphan, Ratanaporn; Phosuya, Chabaphai; Ruanta, Yongyuth; Thavorn, Kednapa; Jamjanya, Sirinda; Chuamanochan, Mati; Nochaiwong, Surapon (Frontiers in Pharmacology, 2023)
Objective: Metformin has recently been demonstrated to have an anti-melanogenic activity. Nevertheless, clinical evidence of the effectiveness of metformin in melasma is lacking. The objective of this study was to assess the efficacy and safety of metformin in the treatment of melasma. Methods: MEDLINE, Embase, PubMed, Cochrane Library (CENTRAL), Scopus, CINAHL, and grey literature databases were searched to 4 October 2022 and updated on 26 February 2023. Randomized controlled trials (RCTs), quasi-RCTs, observational studies, case series, and case reports investigating the efficacy and safety of metformin for melasma were included. The Melasma Area Severity Index (MASI) scores that changed from baseline were pooled using fixed-effects model and expressed as standardized mean differences (SMDs) and 95% confidence intervals (CIs). Results: Three RCTs including 140 patients with melasma were included. The results demonstrated that after 8 weeks, 15% topical metformin significantly reduced the Melasma Area Severity Index (MASI) score compared to placebo (1 trial; n = 60; MD, −0.56; 95% CI, −1.07 to −0.04; p = 0.034). Furthermore, when compared to triple combination cream (TCC), 30% topical metformin demonstrated similar efficacy in reducing the MASI score after 8 weeks (2 trials; n = 80; MD, 0.19, 95% CI, −0.25 to 0.63; p = 0.390). Patients using 30% topical metformin had fewer adverse events compared to TCC users, although no statistical difference was found. Conclusion: Topical metformin was as effective as triple combination cream (TCC) in decreasing changes in the MASI score in patients with melasma, with minimum adverse events. Further studies with larger sample sizes, longer follow-up times, and well-designed trials are required. Systematic Review Registration: Identifier PROSPERO (CRD42022351966).